Assessing use of the South African triage scale in the Western Cape government emergency medical services system - Mould-Millman, Carl Nee-Kofi (Division of General Surgery, 2022)
Introduction: A critical concept underpinning emergency medicine is triage. Triage is the systematic process of sorting patients based on acuity and/or resource need, with the goal of getting the right person to the right place at the right time to receive the right level of care. Triage influences a patient's clinical trajectory, hence impacts both patient outcomes and health system resource utilization. Therefore, the consequences of triage are arguably even more critical in two scenarios: first, early on in the patient's care, such as the prehospital setting; and second, care in resource-constrained health systems, such as in Africa. Prehospital emergency care, delivered by Emergency Medical Services (EMS) providers, represents one of the earliest opportunities for emergency triage of the undifferentiated patient. We conducted a series of projects to, first, understand the current global scientific context of prehospital triage and, next, to better understand how the South Africa Triage Scale (SATS) is used by Western Cape EMS providers for prehospital triage. Findings may help enhance the application of SATS for prehospital triage in the Western Cape. Additionally, findings could provide evidence to encourage the adoption, or rejection, of SATS triage by other EMS systems in resource-constrained settings, especially in Africa. Methods: This project consisted of three distinct objectives which were investigated as separate, but interconnected, studies. The first objective was answered using a secondary research method (a scoping review) designed to discover and appraise existing prehospital triage tools across the world in an effort to better contextualise the specific role filled, and value added, by SATS. The second and third objectives were answered using a quantitative and qualitative approach, respectively, to assess the validity and reliability of SATS among EMS providers, and to understand EMS providers' experiences and perspectives using SATS. We converged the quantitative and qualitative data in a mixed methods analysis. Main results: In the scoping review, we screened 1521 unique articles and completed a full review of 55 articles. We reported that the majority of publications on prehospital triage tools were focused on stroke triage (35%) and trauma triage (35%). There were 15 (27%) publications, corresponding to 11 unique tools, relevant to prehospital triage of undifferentiated patients - overall, the tools had modest triage performance characteristics in high-income settings. However, we found no publications relevant to prehospital triage with SATS in the 2009 to 2019 study period, and no triage tools were studied in low- or middle-income countries. In the quantitative study, we conducted cognitive paper-based SATS triage assessments of 102 EMS providers of all qualifications within the Western Cape Government EMS system. We found a high rate (29.5%) of under-triage and an acceptable rate (13.1 %) of over-triage. Providers' use of the Triage Early Warning Score (TEWS) and the clinical discriminators were often incorrect in 41.4% and 41.2% of cases, respectively. In the qualitative assessment, we completed three focus group discussions with 15 diverse and representative providers from the Western Cape Government EMS system, and we achieved thematic saturation. Four major themes emerged from the discussions: Limited implementation and variable use of SATS; Prehospital effectiveness of SATS; Limitations of the discriminator; and, Special EMS considerations limiting SATS. In general, participants felt SATS was fairly easy to use and an asset in their patient care, explaining that it aided them clinically and with hospital communication. Participants, however, noted that the clinical discriminators were often challenging to apply in the prehospital setting, and the TEWS often did not reflect the patient's true or changing prehospital acuity. The qualitative findings both corroborated and helped explain some of the key quantitative results, with both suggesting that many clinical discriminators are problematic for prehospital use and manually calculating TEWS is an error-prone process for Western Cape EMS providers. Conclusion: SATS is being successfully and innovatively used in the prehospital triage of undifferentiated patients in the Western Cape of South Africa. Researching prehospital SATS in South Africa fills a global scientific gap given we found no reports of prehospital triage tools from low- or middle-income countries. Western Cape EMS participants reported that SATS was generally helpful and relatively easy to use, but reported challenges using TEWS and the clinical discriminators. SATS had good inter-rater reliability, but poor validity. The under-triage rate of 30% was high and attributable to misuse of TEWS and clinical discriminators. The over-triage rate of 13% was acceptable and confirmed by experiences recounted by the EMS participants. Modest adaptations of SATS by expert stakeholders could improve its prehospital performance and utility in the Western Cape Province. SATS for prehospital triage likely has good applicability and utility in other resource-constrained systems, but further adaptation and testing are warranted.